Pengembangan Mobile Learning dengan Aplikasi Padlet untuk Meningkatkan Kemandirian dan Hasil Belajar Geografi Peserta Didik Kelas X IPS di SMA Negeri Surakarta Tahun Ajaran 2021/2022 (Materi Dinamika Hidrosfer dan Dampaknya terhadap Kehidupan) - Adelia Jasmine Nurhalisa; Singgih Prihadi; Sugiyanto Sugiyanto (Universitas Sebelas Maret (UNS), 2023)
The aims of this study were: (1) to analyze the initial conditions of learning independence for class X Social Studies at SMA Negeri 6 Surakarta; (2) Familiarize yourself with mobile learning media with padlet applications on the Hydrosphere Dynamics material and its Impact on the Life of Class X Social Sciences at SMA Negeri 6 Surakarta; and (3) Knowing the effectiveness of mobile learning media with padlet applications to increase the independence and learning outcomes of class X Social Studies students at SMA Negeri 6 Surakarta.The research method used is Research and Development (R&D) with the ADDIE development model. The sampling technique used was simple random sampling and independent learning data collection instruments using questionnaires and observation sheets, learning outcomes about pretest and posttest questions, using media validity validation media, material experts, educators, and individual, small group and field trials.The results showed: (1) The level of learning independence of students in class X IPS is classified as medium and low; (2) Mobile learning with the padlet application to increase independence and learning outcomes was declared suitable for use by media experts (got mode 4), and material experts (got mode 5). The feasibility of this media is also supported by the results of individual trials, small group trials and field trials. (3) Mobile learning media with padlet applications is effective for increasing students' independence and geography learning outcomes. The calculation of the effectiveness of mobile learning with the padlet application is calculated using the Paired Sample T-test formula for a significant level of 5% and the result is that the P Value <0.05.. Keywords: Mobile Learning, Padlet, Hydrosphere, Independent Learning, Learning Outcomes